INTRODUCING ISLAMIC ACCOUNTING STANDARDS AT ISLAMIC BANKS IN GUINEA - Sackor, Muhammed (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study investigates the feasibility and necessity of implementing Islamic accounting standards within the Islamic financial services sector in Guinea, aiming to enhance trust, transparency, and compliance with Shariah principles. Method: A qualitative approach was employed, involving document analysis and expert interviews with Islamic finance practitioners in Guinea to assess the current accounting practices and identify gaps in Shariah-compliant standards. Results: The findings reveal that Islamic banks in Guinea face significant limitations due to the absence of standardized Islamic accounting frameworks, which hinders credibility and operational alignment with Islamic financial principles. Nevertheless, the study identifies considerable opportunities for adopting frameworks such as those proposed by the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI), provided there is institutional support and capacity-building initiatives. Novelty: This paper contributes to the limited literature on Islamic accounting implementation in West Africa by offering a contextual analysis of Guinea’s Islamic banking sector and proposing a practical roadmap for integrating Shariah-compliant financial reporting standards.